Determinant Factors Related to Outcomes in Breast Cancer Survivors: A Systematic Review - Mila Trisna Sari (UMSU, 2025)
Background: The global incidence of breast cancer continues to rise, yet so too does survivorship, due to advances in early detection and treatment. As survivorship improves, understanding the determinants that influence long-term outcomes becomes paramount. Objective: To systematically review and synthesize the current literature on clinical, psychological, social, and socioeconomic factors associated with outcomes in breast cancer survivors. Methods: Following PRISMA guidelines, databases including PubMed, ScienceDirect, Ovid, and Google Scholar were searched for studies published between 1995 and 2023. Determinants were categorized by domain, and only peer-reviewed, original research articles were included. Quality assessment was conducted using the Newcastle-Ottawa Scale. Results: Thirty-three studies involving over 1.3 million breast cancer survivors were included. Key determinants of outcomes included cancer stage, comorbidities, psychological resilience, depression, perceived social support, income, and educational level. The impact of these factors varied across geographical and cultural contexts. Conclusion: Survivorship outcomes in breast cancer are influenced by a complex interplay of biomedical and psychosocial factors. Integrative survivorship care must be tailored to address not only disease characteristics but also individual psychological and social circumstances.